Strain and critical layer thickness analysis of carbon-doped GaAs - Kim, SI; Kim, MS; Min, SK (PERGAMON-ELSEVIER SCIENCE LTD, 1996)
We have calculated the lattice constant, strain, and critical layer thickness of heavily carbon (C)-doped GaAs epilayers as a function of hole concentration. The lattice constant of C-doped GaAs epilayers decreased with increasing hole concentration due to strain by carbon incorporation where carbon has a smaller covalent radii than gallium and arsenic. We also have discussed the relationship between hole concentration and critical layer thickness (L(c)) by the excess stress and Matthews-Blakeslee model. We have calculated not only for the pure case but also 10% compensated case. In compensated epilayers the carbon a toms exist not only on the arsenic sites but also on the gallium sites. As we compared the experimental data of C-doped GaAs with the calculated results, the excess stress model is more agreeable than the Matthews-Blakeslee model. The excess stress, at which surface cross hatching could be seen from the surface, was sigma(exc)/mu = 0.0021 for pure case and 0.0024 for 10% compensated case. Thus we could identify these excess stresses as the critical excess stresses for C-doped GaAs epilayers.
Keywords: P-TYPE GAAS; PHOTOLUMINESCENCE; EPITAXY